Analysis of multiple-dose methotrexate therapy in tubal ectopic pregnancies - İrfan Kutlar; Muhammed Hanifi Bademkıran; Seyhun Sucu; Neslihan Bayramoğlu Tepe; Furkan Çetin (Cukurova Medical Journal, 2022)
Purpose: The study aimed at determining the success rate of sequential multi-dose methotrexate treatment in tubal ectopic pregnancy (EP) patients and the prognostic factors affecting the treatment success. Materials and Methods: Clinical, laboratory, and demographic data of 63 patients -hospitalized with the diagnosis of EP in our tertiary center between 2017-2020 and administered sequential multiple-dose methotrexate treatment protocol- were analyzed in this retrospective study. Results: Based on research findings, medical treatment was successful in 45 of the patients. It was found that 16 out of 18-patient, 88.8% of the patients in the failed group with methotrexate treatment, were operated on due to tubal rupture during follow-up. The mean of sonographic free fluid in Douglas of the successful group with methotrexate treatment was found to be 2.40±0.70 mm (Mean±SE), while it was 10.38±3.05 mm (Mean±SE) in the failed group at the first consultation. The initial β-hCG value of the successful group with methotrexate treatment was measured 3668.55±440.55 IU/L (Mean±SE), while it was 4929.72±752.65 IU/L (Mean±SE) in the failed group. Conclusion: The success rate of the sequential multiple dose methotrexate protocol was 71.4%. Both the initial serum β-hCG level and the amount of sonographic free fluid in the pouch of Douglas were found high in the failed group with medical treatment at the first consultation.